Taxonomic changes in the Neotropical Arctiinae, Arctiini (Lepidoptera, Erebidae) relating to the fauna of Trinidad and Tobago - Cock, Matthew J.w.; Laguerre, Michel (Zootaxa, 2021)
In preparation for a general account of the Trinidad and Tobago Arctiini, the following taxonomic changes are made and justification provided. A lectotype is designated for Castrica sordidior Rothschild, 1909. Castrica oweni Schaus, 1896, stat rev. is returned to species rank. The following new synonyms are established: Castrica sordidior Rothschild, 1909 syn. nov. of Castrica oweni Schaus, 1896; Automolis nigroapicalis Gaede, 1923, Automolis semicostalis Rothschild, 1909, Automolis alboatra Rothschild, 1909, Automolis alboatra borussica Seitz, 1922, Sallaea unifascia Druce, 1899, Automolis hamifera Dognin, 1907, and Automolis apicata Schaus, 1905 syn. nov. of Pryteria costata Möschler, 1883; and Sphinx Adfeit. psamas Cramer, [1779] syn. nov. of Phalaena Noctua onytes Cramer, [1777]. Virbia birchi Druce, 1911 is confirmed to be a synonym of Phalaena medarda Stoll, [1781]. Pryteria tenuis (Rothschild, 1935) stat. nov. and P. intensa (Rothschild, 1935) stat. nov. are raised to species level pending clarification of the genus Pryteria in Central America.